Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/jnnp-2016-313766
|View full text |Cite
|
Sign up to set email alerts
|

Bedside cerebral microdialysis monitoring of delayed cerebral hypoperfusion in comatose patients with poor grade aneurysmal subarachnoid haemorrhage

Abstract: In comatose patients with SAH, delayed cerebral hypoperfusion correlates with a CMD pattern of lactate increase and simultaneous glucose decrease. CMD abnormalities became apparent in the hours preceding PCT, thereby suggesting that CMD monitoring may anticipate targeted therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
0
31
0
3
Order By: Relevance
“…Several studies investigated metabolic changes associated with parameters of cerebral perfusion, including CBF, CPP, and imaging surrogates. In summary, a negative correlation between CBF and CMD-lactate, CMD-LPR, CMD-glutamate, and CMD-glycerol has been described, while CMD-pyruvate and CMD-glucose are commonly positively correlated with CBF ( 25 , 31 , 32 , 35 , 38 40 ). Other studies focused on DCI and found increases in CMD-lactate and CMD-glutamate as early sensitive markers ( 17 ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Several studies investigated metabolic changes associated with parameters of cerebral perfusion, including CBF, CPP, and imaging surrogates. In summary, a negative correlation between CBF and CMD-lactate, CMD-LPR, CMD-glutamate, and CMD-glycerol has been described, while CMD-pyruvate and CMD-glucose are commonly positively correlated with CBF ( 25 , 31 , 32 , 35 , 38 40 ). Other studies focused on DCI and found increases in CMD-lactate and CMD-glutamate as early sensitive markers ( 17 ).…”
Section: Resultsmentioning
confidence: 90%
“…Other studies focused on DCI and found increases in CMD-lactate and CMD-glutamate as early sensitive markers ( 17 ). Metabolic derangement with increasing CMD-LPR (> 40) and decreasing CMD-glucose (< 0.7 mmol/l) may occur up to 16 h before DCI onset ( 26 , 32 ). In the following, we give detailed information on some studies, all studies are listed in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CMD markers—such as glucose and L/P ratio—may be good surrogate markers of CBF, and indeed this has recently been confirmed by several clinical studies combining microdiaylsis with brain imaging, both in patients with SAH ( 37 39 ) and TBI ( 40 ). A recently published small observational cohort study illustrated the potential value of CMD monitoring to help detecting cerebral hypoperfusion in comatose aSAH patients, in whom, the clinical examination was unreliable ( 37 ). This study stressed the importance of following dynamic trends over time of both CMD L/P ratio and glucose for the timely detection of secondary cerebral ischemic insults.…”
Section: Cmd To Guide Individualized Intensive Care Therapymentioning
confidence: 77%